Multiple Drivers of High Species Diversity and Endemism Among Alyssum Annuals in the Mediterranean: The Evolutionary Significance of the Aegean Hotspot - Cetlová, Veronika; Zozomová-Lihová, Judita; Melichárková, Andrea; Mártonfiová, Lenka; Španiel, Stanislav (Frontiers in plant science, 2021)
The Mediterranean Basin is a significant hotspot of species diversity and endemism, with various distribution patterns and speciation mechanisms observed in its flora. High species diversity in the Mediterranean is also manifested in the monophyletic lineage of Alyssum annuals (Brassicaceae), but little is known about its origin. These species include both diploids and polyploids that grow mainly in open and disturbed sites across a wide elevational span and show contrasting distribution patterns, ranging from broadly distributed Eurasian species to narrow island endemics. Here, we investigated the evolution of European representatives of this lineage, and aimed to reconstruct their phylogeny, polyploid and genome size evolution using flow cytometric analyses, chloroplast and nuclear high- and low-copy DNA markers. The origin and early diversification of the studied Alyssum lineage could be dated back to the Late Miocene/Pliocene and were likely promoted by the onset of the Mediterranean climate, whereas most of the extant species originated during the Pleistocene. The Aegean region represents a significant diversity center, as it hosts 12 out of 16 recognized European species and comprises several (sub)endemics placed in distinct phylogenetic clades. Because several species, including the closest relatives, occur here sympatrically without apparent niche differences, we can reject simple allopatric speciation via vicariance as well as ecological speciation for most cases. Instead, we suggest scenarios of more complex speciation processes that involved repeated range shifts in response to sea-level changes and recurrent land connections and disconnections since the Pliocene. In addition, multiple polyploidization events significantly contributed to species diversity across the entire distribution range. All seven polyploids, representing both widespread species and endemics to the western or eastern Mediterranean, were inferred to be allopolyploids. Finally, the current distribution patterns have likely been affected also by the human factor (farming and grazing). This study illustrates the complexity of evolutionary and speciation processes in the Mediterranean flora.
Keywords: endemics; allopolyploidy; Mediterranean; Alyssum; phylogeny; sympatry; Aegean area; annual species